Polysaccharide storage myopathy in two Percheron horses Miopatia por acúmulo de polissacarídeo em dois equinos da raça Percheron - de Souza Teixeira M.B.* (2023)
© 2023 Universidade Federal de Santa Catarina. All rights reserved.Polysaccharide storage myopathy (PSSM) is a genetic disorder or by undetermined cause characterized by the abnormal accumulation of glycogen and polysaccharides in skeletal muscle fibers. The present report describes two Percheron horses, from different properties in the municipality of Pouso Redondo - SC, with locomotor clinical signs that started after work. The clinical signs observed were rigid gait, mainly of the pelvic limbs, muscle weakness, and recumbency. In the first case, the animal was diagnosed with severe multifocal rhabdomyonecrosis, moderate multifocal myoglobin nephrosis and severe diffuse transmural fibrinonecrotic gastritis. PSSM was confirmed by the presence of polysaccharide inclusions in myofiber sarcolemma visualized by periodic acid-Schiff (PAS) staining. In the second case, the horse presented two episodes of muscle disorder after work. The therapeutic protocol was based on penicillin, flunixin meglumine and fluid therapy with ringer lactate. An increase in creatine kinase (669.0 UI/L) and aspartate aminotransferase (669.0 UI/L) was observed in the serum biochemical evaluation. Research for mutation in the GYS1 gene was performed, with a positive heterozygote result. After rest and gradual recovery, the horse was only submitted to light work, with no return of the clinical condition since then. Thus, this report describes two cases of PSSM with distinct clinical evolution and diagnostic methods.